Randomised controlled trial to assess the effectiveness of apnoeic oxygenation in adults using low-flow or high-flow nasal cannula with head side elevation versus usual care to prevent desaturation during endotracheal intubation in the emergency department (ApOxED): study protocol. Issue 11 (16th November 2020) - Waheed, Shahan; Kapadia, Nazir Najeeb; Khan, Muhammad Faisal; Kerai, Salima Mansoor; Raheem, Ahmed; Naeem, Rubaba
Abstract : Introduction: Apnoeic oxygenation is a process of delivering continuous oxygen through nasal cannula during direct laryngoscopy. The oxygen that is delivered through these nasal cannulas is either low flow or high flow. Although the effectiveness of apnoeic oxygenation has been shown through systematic reviews and randomised controlled trials, a comparison of high-flow versus low-flow oxygen delivery has not been tested through a superiority study design. In this study we propose to assess the effectiveness of giving low-flow oxygen with head side elevation versus high-flow oxygen with head side elevation against the usual practice of care in which no oxygen is provided during direct laryngoscopy. Methods and analysis: This will be a three-arm study instituting a block randomisation technique with a sample size of 46 in each arm (see table 1 ). Due to the nature of the intervention, no blinding will be introduced. The primary outcomes will be lowest non-invasive oxygen saturation measurement during direct laryngoscopy and during the 2 min after the placement of the tube and the first pass success rate. The intervention constitutes head side elevation up to 30° for improving glottis visualisation together with low-flow or high-flow oxygen delivery through nasal cannula to increase safe apnoea time for participants undergoing endotracheal intubation. Primary analysis will be intention to treat. Ethics and dissemination: The study is approved by the Ethical Review Committee of Aga Khan University Hospital (2019-0726-2463). The project is an institution University Research Committee grant recipient 192 002ER-PK. The results of the study will be disseminated among participants, patient communities and healthcare professionals in the institution through seminars, presentations and emails. Further, the findings will be published in a highly accessed peer-reviewed medical journal and will be presented at both national and international conferences. Trial registration number: ClinicalTrials.gov Registry (NCT04242537 ).